PENGARUH MEDIA LAGU TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 007 SUNGAI PINANG - Ade Lilis Suryani; Sukriadi; Muhlis; Andi Asrafiani Arafah; Muhammad Sultan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to find out how the use of song media affects the mathematical learning results of students geometric concepts classroom V SD State 007 Sungai Pinang. This research is done using quantitative methods with experimental quasics. The data collection technique used is with tests. The tests used in this research are pre-test and post-test that have been tested for validity and reliability. In this study, the t test was used to analyze data that had been distributed normally and homogeneously. The results of the study showed that the mathematical learning results in the experimental class obtained an average score of 78.25, whereas in the control class the average score was 65.65. The data analysis performed using the t (Independent Sample t-Test) with the program SPSS 25.0 indicated that the sig value (2-tailed) = 0.001. Based on the decision-making of the Independent t-test, Hα was accepted and H0 was rejected. Therefore, since the sig (2-tailed) is less than 0.05, it can be concluded that there is or is an influence of the media of the song on the mathematical learning outcomes of the student geometric material classroom V SD State 007 Sungai Pinang school year 2023/2024.